Effect of electric field on the morphology and mechanical properties of electrospun fibers. Issue 56 (24th May 2016) - Li, Xiang; Bian, Fenggang; Lin, Jinyou; Zeng, Yongchun
Abstract : Three kinds of spinnerets containing single needle, sharp and blunt cones were used to study the effect of electric field distribution on the morphology and mechanical properties of the as-prepared fibers. Abstract : In this work, two kinds of conical spinnerets, referred to as the sharp cone and blunt cone, were compared to the single needle spinneret to investigate the effect of electric field distribution on the morphology and mechanical properties of the as-prepared fibers. Based on the simulation results, polystyrene and poly(vinylidene fluoride) solutions were used in the experiments. The electric field distributions were simulated, and the jet paths were captured by a high-speed camera. Meanwhile, the morphology and mechanical properties of the as-prepared fibers were characterized. It was found that the as-prepared fibers' morphology induced by these different spinnerets had a significant influence on the mechanical properties. It is worth mentioning that the mechanical properties of fiber mats were improved from the sharp cone electrospinning system, which lays the foundation for the regulatory of fiber structures.